Effectiveness of booklet and digital education media on parents’ ability to care for children with leukemia undergoing chemotherapy: A systematic literature review - Khansa Rizki Syukrina; Yufitriana Amir; Reni Zulfitri (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Leukemia is the most common childhood cancer and requires prolonged chemotherapy, which often causes side effects that must be managed at home. Parents play a crucial role in supporting treatment adherence and symptom management; however, inadequate knowledge and caregiving skills remain significant challenges. Health education using booklet and digital media has been increasingly implemented to improve parental caregiving competence. Purpose: To compare the effectiveness of booklet and digital education media in improving parents’ ability to care for children with leukemia undergoing chemotherapy. Method: A systematic literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Literature searches were performed in PubMed, ScienceDirect, and Google Scholar databases. Articles published between 2021 and 2025 in English were included if they evaluated educational interventions using booklet or digital media for parents or caregivers of children with leukemia. A total of 65 records were identified, and 11 studies met the inclusion criteria for final analysis. Results: The eleven studies evaluated various educational interventions using booklet-based and digital media among parents and caregivers of children with leukemia. Several studies reported improvements in caregiver knowledge, readiness, self-efficacy, symptom management, and caregiving skills following educational interventions. Digital media demonstrated advantages in accessibility, interactivity, and continuous support, whereas booklet-based education facilitated information retention and repeated learning. Conclusion: The findings suggest that both booklet-based and digital educational media may contribute to improving parental knowledge, readiness, and caregiving skills in caring for children with leukemia undergoing chemotherapy. However, the effectiveness of these interventions varied across studies due to differences in study design, intervention characteristics, and outcome measures. A combination of booklet and digital educational media may provide complementary benefits in supporting parental education and home-based care. Suggestion: Healthcare providers may consider integrating both booklet-based and digital education media as a complementary approach when delivering health education to parents of children with leukemia undergoing chemotherapy. Such an approach may combine the advantages of information retention offered by booklets with the accessibility and interactivity of digital platforms. Future research should evaluate the long-term effectiveness of hybrid educational interventions using rigorous study designs and explore the development of culturally appropriate, interactive, and user-friendly digital platforms to enhance parental engagement, caregiving competence, and home-based care outcomes.